Utilization Rates of Scad (Decapterus spp.) in Banda Sea where landed in Ocean Fishery Harbor Kendari, Southeast Sulawesi - Hute, Endang Rahmi; Asriyana, Asriyana; Ramli, Muhammad (Universitas Halu Oleo, 2021)
Scads fish (Decapterus spp.) is an economically important fish and is one of the target catches in the Banda Sea waters. This study aims to analyze utilization rates of scads fish in the Banda Sea waters landed at the Ocean Fisheries Harbor (PPS) Kendari in terms of the trend of catch per unit effort (CPUE). The study was conducted from January to June 2018. Analysis of data included capture productivity (CPUE), surplus production models, utilization rates, and the number of scad fish catches allowed in the Banda Sea waters. The results showed that the average catch productivity (CPUE) was 1.79 tons/trip. The sustainable catch of scad fish in the Banda Sea waters is 6,313.10 tons with an optimum effort of 4,419 trips/year. The average utilization rate is 90.98% of the MSY value and the total allowable catch (TAC) is 5,050.48 tons. High utilization rates and exceeding sustainable catches indicate that scad fishery in the Banda Sea has been heavily exploited. Control of fishing efforth both total of trips, fishing gear, and decent size of scad are necessary to reduce fishing pressure of this species.